2013
DOI: 10.1038/onc.2013.389
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of paxillin confers cisplatin resistance in non-small cell lung cancer via activating ERK-mediated Bcl-2 expression

Abstract: Paxillin (PXN) is required for receptor tyrosine kinase-mediated ERK activation, and the activation of the Raf/MEK/ERK cascade has been linked with Bcl-2 expression. We hypothesized that phosphorylation of PXN by the EGFR/Src pathway might contribute to cisplatin resistance via increased Bcl-2 expression. We show that cisplatin resistance was dependent on PXN expression, as evidenced by PXN overexpression in TL-13 and TL-10 cells and PXN knockdown in H23 and CL1-5 cells. Specific inhibitors of signaling pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 43 publications
6
58
1
1
Order By: Relevance
“…Therefore, Bcl-2 expression is the key step to protect cells from apoptosis in melanoma. It has a crucial role in chemoresistance in various human cancers (22,23). The present study detected expression of Bcl-2 at 24 h after treatment with the inhibitors.…”
Section: Discussionsupporting
confidence: 49%
“…Therefore, Bcl-2 expression is the key step to protect cells from apoptosis in melanoma. It has a crucial role in chemoresistance in various human cancers (22,23). The present study detected expression of Bcl-2 at 24 h after treatment with the inhibitors.…”
Section: Discussionsupporting
confidence: 49%
“…Several studies have shown that PXN plays an important role in regulating tumor cell proliferation and mediating signal transduction of epidermal growth factor (EGF) (2,(10)(11)(12). Various scholars have also demonstrated that PXN leads to resistance to drugs by inhibiting the apoptosis of cancer cells in non-small cell lung cancer (17). In the present study, following treatment of cetuximab in SW480 and Caco-2 cells for a period of time, the expression of PXN in SW480 cells declined at first, and then gradually increased and finally stabilized, which was consistent with the proliferation rate.…”
Section: Discussionmentioning
confidence: 99%
“…As for the mechanisms, it is assumed that PXN plays a role in regulating the signaling pathway in the downstream of KRAS. As described in the Introduction, activation of the ERK signaling pathway requires the participation and mediation of PXN in prostate cancer and non-small cell lung cancer (10,17 (11). Several studies have demonstrated that Erk always gives a positive feedback on PXN and plays an important part in the activitation of PXN and interaction between FAK and PXN (11,22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA extraction and reverse transcriptase reaction were described previously. 8 The following primer sequences were used for amplification of the Bcl-2 gene: the forward primer, 5′-CTGTGGATGACTGAGTACC-3′ and the reverse primer, 5′-CAGCCAGG AGAAATCAAAC-3′.…”
Section: Discussionmentioning
confidence: 99%